2007
DOI: 10.2166/wst.2007.237
|View full text |Cite
|
Sign up to set email alerts
|

A one-stage system with partial nitritation and Anammox processes in the moving-bed biofilm reactor

Abstract: The ability of bacterial cultures to create biofilm brings a possibility to enhance biological wastewater treatment efficiency. Moreover, the ability of Anammox and Nitrosomonas species to grow within the same biofilm layer enabled a one-stage system for nitrogen removal to be designed. Such a system, with Kaldnes rings as carriers for biofilm growth, was tested in a technical pilot plant scale (2.1 m(3)) at the Himmerfjärden Waste Water Treatment Plant (WWTP) in the Stockholm region. The system was directly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 10 publications
4
27
0
Order By: Relevance
“…Similar observations were also reported by Chamchoi and Nitisoravut [12] and Strous et al [27]. However in contrast to this, various workers have reported an increase in effluent pH during Anammox activity [19,31,32]. As per the stoichiometry in Eq.…”
Section: Maintenance Of Anammox Activitysupporting
confidence: 86%
“…Similar observations were also reported by Chamchoi and Nitisoravut [12] and Strous et al [27]. However in contrast to this, various workers have reported an increase in effluent pH during Anammox activity [19,31,32]. As per the stoichiometry in Eq.…”
Section: Maintenance Of Anammox Activitysupporting
confidence: 86%
“…The phenomenon of a significant increase in effluent pH for Anammox bioreactors was also reported by Liu et al [22]. Szatkowska et al [23] proposed that the Anammox process can increase the pH value to some extent due to cellular synthesis. However, Strous et al [6] reported that the pH variation in one cycle of a SBR was not large.…”
Section: Ph Increase and Inhibition Analysissupporting
confidence: 56%
“…The optimal pH range of anammox bacteria is within 7.7-8.2 (Strous et al 1997). Various researchers have reported an increase in effluent pH along with increase in anammox activity (Tang et al 2009;Liu et al 2008;Szatkowska et al 2007). On the other hand, Strous et al (1997) showed that the specific anammox activity at pH of 9 was only 1/5 of that at pH of 8.…”
Section: Effect Of Ph and Inhibition Of Free Ammoniamentioning
confidence: 99%